In-utero, incarcerated umbilical hernia with fistula - Vincent Adjetey; Stephen P. Almond; VanHenry Savell (Elsevier, 2020)
Omphalocele, gastroschisis, and umbilical hernia are abdominal wall defects well-characterized by their clinical presentation, umbilical cord position, treatment options, and clinical course. Differentiating omphalocele from umbilical cord hernia can be challenging. To our knowledge this is the first case of an incarcerated umbilical hernia with a fistula that may have originated in-utero.